Wybrane meandry procesów cyfryzacji polskiej oświaty - Janczyk, Janusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
W perspektywie kilkunastu ostatnich lat wdrażano ICT na wielu płaszczyznach w polskiej oświacie. Procesy cyfryzacji są kolejnym etapem unowocześnienia szkolnych procesów kształcenia. Dla tej publikacji ważniejsze są cienie tychże zmian, niż ich niewątpliwe blaski. Z wielu zagrożeń, które czyhają na drodze do nowoczesnej edukacji, wybrano te, które były już sygnalizowane we wcześniejszych etapach modernizacji. W wybranych aspektach widoczna jest pełna analogia do zjawisk, które miały miejsce w pierwszych etapach wdrażania Internetu do polskich szkół.

In the last several years we implemented ICT in many areas in the Polish education. Digitization processes are next step in the modernization of school learning processes. For this publication more important are the shadows of these changes, than their undoubted brilliance. Of the many threats, that lurk on the way to modern education, we selected the ones, that had already been signaled in the earlier stages of modernization. In some respects can be seen full analogy to the events that took place in the early stages of implementation of the Internet to Polish schools.
Selected meanders process of digitization polish education
Keywords: nauczyciel; ICT; kompetencje; competences